PENANGGULANGAN PENCEMARAN TELUK JAKARTA UNTUK MENURUNKAN EMISI KARBON - Falih Alghoniy Taftazani (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Carbon emissions are the combustion of compounds that have carbon content, such as diesel, LPJ, CO2, and other fuels. The combustion causes the release of gases which, when excessive, cause climate change followed by greenhouse gas emissions. It is undeniable that carbon emissions are the cause of the earth's temperature becoming hotter. To determine the amount of carbon emissions, carbon footprint measurements are made by reporting the activities of individuals or other entities, such as companies, countries, buildings and others. The ocean is a vital support in a changing climate, absorbing about a quarter of all carbon dioxide emissions produced by living things. The ocean also absorbs nearly 100% of the Earth's heat, and carbon dioxide absorption is divided into two: active and passive absorption. However, in passive absorption, if the sea absorbs too much carbon, the sea can no longer accommodate carbon so that the sea releases carbon which is then helped by active absorption of carbon using phytoplankton which is also supported by sunlight but there are still obstacles in phytoplankton absorbing carbon such as heavy metal pollution and plastic waste. To overcome this pollution comes bioremediation technology by controlling heavy metals from seawater contaminants. In addition, the presence of mangroves can block plastic waste from drifting into the sea but too much plastic waste in mangroves makes the mangrove ecosystem die. Therefore, the need for public awareness to take part in tackling seawater pollution because when people continue to pollute seawater technology is not always the solution to overcome this due to technological limitations in tackling seawater pollution.